Impact of permittivity grading on coupled resonance in hybrid-ENZ metasurfaces - Anindita Das; Laura C Wynne; Andrea Di Falco; Sebastian A Schulz (JPhys Photonics)
Hybrid-epsilon-near-zero (ENZ) metasurfaces, consisting of nanoantenna arrays on thin films of ENZ materials, feature a coupled resonance spectrum and have gathered significant interest for their nonlinear optical properties and their use in electro-optically tunable metasurfaces. While typically assumed to have a uniform permittivity, the ENZ film often features a graded permittivity distribution as a consequence of either material growth or capacitive tuning. Here we assess the impact of such a permittivity grading on the coupled resonance spectrum and show that the presence of grading alone results in a strong shift of the transmission minima of the coupled resonance, providing a new design parameter for hybrid-ENZ metasurfaces.